2018
DOI: 10.1051/matecconf/201819708009
|View full text |Cite
|
Sign up to set email alerts
|

Determining the energy demand towards sustainable machining of AISI 316L stainless steel

Abstract: Minimizing the energy demand of machining operations has become mainly in the manufacturing field; encouraged by the significantly increase in the energy cost and the environmental effects due to high levels of energy demand. The energy consumed to cutting operation in turning process was divided into two sections, i.e. the energy used to setup machine and the energy consumed to cutting process. The total energy demand of machining process can be estimated with prediction equations based on material removal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The researchers suggested that the overall energy need of environmentally friendly turning process cutting activities be estimated and computed. [4]. Metal cutting now makes use of nanotechnology to improve cooling efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers suggested that the overall energy need of environmentally friendly turning process cutting activities be estimated and computed. [4]. Metal cutting now makes use of nanotechnology to improve cooling efficiency.…”
Section: Introductionmentioning
confidence: 99%